The Effect of White Cells on Platelet Aggregation - Harrison, M. J. G; Emmons, P. R; Mitchell, J. R. A (Thrombosis and Haemostasis, 1966)
The effect of white cells on platelet aggregation has been studied. White cells have little or no effect on nor-adrenaline induced clumping, produce disaggregation of ADP, 5HT and thrombin induced clumping, and first enhance and then reverse ATP induced clumping. The effects of white cells on clumping are similar to their effects on the clumping agents themselves, for they do not inactivate nor-adrenaline, but rapidly inactivate ADP, and produce a more active agent from ATP. In respect of the patient to patient variability in clumping activity, the amount of aggregation produced by ATP is very closely related to the white cell content of the PRCP, whereas the variations in ADP induced clumping must be due to other factors. The significance of these findings for the possible role of the platelet clumping agents in arterial thrombosis is discussed.